Ranitidine pharmacokinetics in newborn infants. Issue 5 (May 1993) - Fontana, M; Massironi, E; Rossi, A; Vaglia, P; Gancia, G P; Tagliabue, P; Principi, N
Abstract : Few data are available for ranitidine pharmacokinetics in the first few days of life. Twenty seven newborn infants were treated with intravenous ranitidine because they were vomiting blood, although they had a negative Apt's test. Each infant provided two blood samples at randomly selected times 30-360 minutes after a 2.4 mg/kg intravenous bolus of ranitidine. A single exponential equation for the concentration-time graph was fitted to the mean serum concentrations at different times. From this model the following mean (SD) measurements wer derived: elimination half life, 207.1 (19.1) minutes; total volume of distribution, 1.52 (0.91) l/kg; and total plasma clearance, 5.02 (0.46) ml/kg/min. Assuming that these measurements do not change with different administered doses, regimens can be derived to assist in planning ranitidine treatment in newborn infants.